2021
DOI: 10.2217/fon-2020-0577
|View full text |Cite
|
Sign up to set email alerts
|

Potential Utility of Peptides Against Damage Induced by Ionizing Radiation

Abstract: Radioprotection is the process whereby biological systems are aided against undesirable radiation hazards. Primitive radioprotectors suffered from either having crucial side effects or low efficacy in clinical applications. Therefore, the search for less toxic but more capable radioprotectants has continued for decades. Peptides have been investigated as radioprotectants in a variety of preclinical models both in vitro and in vivo. Peptides exert their influence through scavenging free radicals, modifying cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Several vitamin approaches mentioned above are covered in detail in another paper in this issue (Singh et al). Dietary supplementation with Bowman-Birk protease inhibitors derived from soybeans ( Shaghagi et al, 2021 ; Kennedy, 2021 ), L-selenomethionine, or a combination of selected antioxidant agents ( Guan et al, 2004 ; Kennedy et al, 2007 ) has shown promise to prevent the decrease in antioxidants in the plasma of mice exposed to proton or HZE particle radiation. Adding nutritional foods, such as blueberries, to crew diets may provide added benefits to help reduce ROS and mitigate radiation-induced CNS effects, as reported in animal studies using space-relevant radiation exposures ( Poulose et al, 2017 ).…”
Section: Overlapping Mechanisms Of Radiation Injury Drug Classes With...mentioning
confidence: 99%
“…Several vitamin approaches mentioned above are covered in detail in another paper in this issue (Singh et al). Dietary supplementation with Bowman-Birk protease inhibitors derived from soybeans ( Shaghagi et al, 2021 ; Kennedy, 2021 ), L-selenomethionine, or a combination of selected antioxidant agents ( Guan et al, 2004 ; Kennedy et al, 2007 ) has shown promise to prevent the decrease in antioxidants in the plasma of mice exposed to proton or HZE particle radiation. Adding nutritional foods, such as blueberries, to crew diets may provide added benefits to help reduce ROS and mitigate radiation-induced CNS effects, as reported in animal studies using space-relevant radiation exposures ( Poulose et al, 2017 ).…”
Section: Overlapping Mechanisms Of Radiation Injury Drug Classes With...mentioning
confidence: 99%
“…Kidney is an IR sensitive organ because the function and morphology of kidney as well as phenotype of kidney cells are affected by IR [12]. Several investigations have reported the protective effects of antioxidants scavenging free radicals as radio protectors [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%